Can government policies reverse undesirable declines in fertility? - Elizabeth Brainerd (IZA World of Labor, 2014)
Since 1989 fertility and family formation have declined sharply in Central and Eastern Europe and the former Soviet Union. Fertility rates are converging on—and sometimes falling below—rates in Western Europe, most of which are below replacement levels. Concerned about a shrinking and aging population and strains on pension systems, governments are using incentives to encourage people to have more children. These policies seem only modestly effective in countering the impacts of widespread social changes, including new work opportunities for women and stronger incentives to invest in education.
Keywords: J13; J18; P36; 330; fertility; pronatalist policies; transition economies